Safeguarding Malaysian Heritage Food (MHF): the impact of Malaysian food culture and tourists’ food culture involvement on intentional loyalty - Omar, Siti Radhiah; Ab Karim, Shahrim; Abu Bakar, Ainul Zakiah; Omar, Siti Nazirah (Elsevier, 2015)
Cultural heritage food experiences in tourism destination hold a boundless impression on tourists’ loyalty towards a destination. The researchers conducted a survey on 100 international tourists and used multiple regression analysis to verify the factors affecting the intentional loyalty on heritage food consumption. Consequently, this study encountered that both Food Culture Involvement and Malaysian Food Culture had impact on tourists’ Intentional Loyalty that involves revisiting Malaysia and repurchasing MHF. Also, this research outlines substantive recommendations on marketing strategies specifically for food providers to market MHF in establishing Malaysia as the distinctive food tourism destination in the eyes of the world.